Effects of handgrip strength training on menopausal symptoms among active and inactive elderly community women - Agraj'ma, Arkana Shalihat; Norlinta, Siti Nadhir Ollin; Tsai, YuChuan; Jannah, Suci Muqodimatul (JHeS (Journal of Health Studies), 2026)
Menopausal symptoms can reduce quality of life in elderly women and their severity is influenced by physical activity levels. In European regions approximately 70-80% women experiencing menopausal symptoms, whereas in America the proportion is around 60% and in Asia, reports indicate that approximately 10% of women in Japan and Indonesia experience menopausal symptoms. Hand grip training as a form of resistance training has the potential to increase muscle strength and help reduce menopausal symptoms. This study aims to evaluate the effect of hand grip training on menopausal symptoms in active and inactive elderly women in the community. The study used a  quasi-experimental pre-test and post-test two-group design consisting of 34 elderly women aged 50–60 years who were divided into active and inactive groups based on their physical activity levels using the International Physical Activity Questionnaire Short Form (IPAQ-SF) questionnaire. The hand grip training intervention was given for 4 weeks with a frequency of 3 times per week for 12 training sessions. Menopausal symptoms were measured using the Menopause Rating Scale (MRS). Data were analyzed using the Wilcoxon Signed Rank Test for the active group and Paired Sample T-Test for the inactive group. In the active group, the median MRS scored decreased from 7.00 to 6.00 (p=0.001). In the inactive group, the mean MRS scored decreased from 12.24±3.80 to 8.53±3.52 (p=0.000). Hand grip training siginificantly reduces menopausal symptoms in both active and inactive elderly with greater improvement observed in the inactive group. This simple exercise can be effectively implemented in community-based settings to help manage menopausal symptoms among postmenopausal elderly women.